Improvement of Tops Spinning manufacturing with CNC Lathe - Sulaiman, Shamsuddin; Tang, Sai Hong; Pawanchi, Sohaimi; Esmaeilian, Gholamreza; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah (Elsevier, 2011)
This paper presents an increasing demand of Top-Spinning (T-S) has resulted in the production of high quantity of T-S. Currently, the production of T-S is very low and not up to the required demand. This is due to the old machine used as well as an old method in the manufacturing of T-S, which lead to the longer time taken compared to the new technology found in this project. The cardinal purpose of this project is to identify the machining sequence with the selection of a suitable tool and reducing machining cycle time with the use of CNC Lathe for manufacturing T-S. In ensuring a successful and optimum result of the project, manufacturing T-S with CNC Lathe will be assisted by Mathematisch Technishe software Entwicklung (MTS) and Master CAM simulation to determine machining sequence, cutting tools, technology parameters and machining cycle time. The data extracted from MTS, and CAD/CAM simulation process will then be used for manufacturing T-S on CNC Lathe technology. This project emphasizes on the importance of determining machining sequence, cutting tools to manufacture T-S in any shape available and also resolving machining cycle time. The result from MTS and CAD/CAM with three analyses of machining sequence, cutting tool and technology parameters will be used to proceed on CNC Lathe. Finally, with the utilization of the data extracted from MTS software, and CAD/CAM simulation has successfully impacted the reduction on overall machining cycle time while producing T-S.